Customer satisfaction on service quality of University Veterinary Hospital (UHV) feline section, Universiti Putra Malaysia (UPM) : application of SERVQUAL model - Marji, Marlia (2016)
Service quality is an assessment of how well a delivered service fit to the customers’ expectations. It is important to measure service quality to ensure delivered service meets customer satisfaction. Service quality can be measured using the SERVQUAL model. There have not been any studies thus far investigating service quality in veterinary hospitals. Therefore, this study was conducted to measure service quality in the Feline section of University Veterinary Hospital (UVH), Universiti Putra Malaysia (UPM) to identify areas to improve performances. This study was conducted at the Feline section for four weeks. Two sets of questionnaires based on the SERVQUAL model were given to the customers. The first set of questionnaire is on customers’ expectations of veterinary hospitals in general, while the second set of questionnaire is on customers’ perceptions of UVH. The SERVQUAL model measures service quality based on gap score (GS) of five dimensions which are tangibles, reliability, responsiveness, assurance and empathy. A gap score on each dimensions was computed based on the following formula; GS = Perception (P) – Expectation (E). 89 respondents participated in this study. Customers’ perceptions do not meet customers’ expectations in all five dimensions. There was a significant difference in mean of expectations and mean of perceptions (P< 0.05) in all dimensions except for empathy. The lowest gap scores were exhibited by tangible (-0.176) and empathy (-0.140) dimensions. The highest gap scores were exhibited by reliability (-0.494) and responsiveness (-0.431) dimensions. Although assurance dimension had a gap score of -0.281, UVH have closely met the customers’ high expectations in this dimension. UVH should invest to improve its reliability and responsiveness dimensions for better performances in service quality.